2013
DOI: 10.1111/jam.12111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diffusion and dilution methods to determine the antimicrobial activity of water-soluble chitosan derivatives

Abstract: Aims: Chitosan has gained wide applications in the food industry and biomedical field owing to its biodegradability, biocompatibility, nontoxicity and its antimicrobial activity against a wide spectrum of micro-organisms. However, the methods used to investigate antimicrobial effects of chitosan vary considerably among studies, making comparisons difficult. Methods and Results: One diffusion (disc diffusion) and two dilution (agar dilution and broth microdilution) methods commonly used in clinical laboratories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 39 publications
(114 reference statements)
1
41
0
1
Order By: Relevance
“…It was found that chitosan was more effective than some traditional antibiotics used as amoxicillin, chloramphenicol and sulfamethoxazole, and those ofAsan-Ozusaglam et al (2016) supported this result. There were strong variations in chitosan antimicrobial activity results which is supported by many findings revealing that the antimicrobial activity of chitosan is dependent upon the physicochemical nature of chitosan, the conditions of the chitosan production process, the testing method and bacterial genus/species tested(Jiang et al, 2012;Younes et al, 2014).As it was noticed, chitosan exhibited very similar activities against fish pathogenic bacteria in a range of 13.02-13.88 mm. There were strong variations in chitosan antimicrobial activity results which is supported by many findings revealing that the antimicrobial activity of chitosan is dependent upon the physicochemical nature of chitosan, the conditions of the chitosan production process, the testing method and bacterial genus/species tested(Jiang et al, 2012;Younes et al, 2014).As it was noticed, chitosan exhibited very similar activities against fish pathogenic bacteria in a range of 13.02-13.88 mm.…”
mentioning
confidence: 62%
“…It was found that chitosan was more effective than some traditional antibiotics used as amoxicillin, chloramphenicol and sulfamethoxazole, and those ofAsan-Ozusaglam et al (2016) supported this result. There were strong variations in chitosan antimicrobial activity results which is supported by many findings revealing that the antimicrobial activity of chitosan is dependent upon the physicochemical nature of chitosan, the conditions of the chitosan production process, the testing method and bacterial genus/species tested(Jiang et al, 2012;Younes et al, 2014).As it was noticed, chitosan exhibited very similar activities against fish pathogenic bacteria in a range of 13.02-13.88 mm. There were strong variations in chitosan antimicrobial activity results which is supported by many findings revealing that the antimicrobial activity of chitosan is dependent upon the physicochemical nature of chitosan, the conditions of the chitosan production process, the testing method and bacterial genus/species tested(Jiang et al, 2012;Younes et al, 2014).As it was noticed, chitosan exhibited very similar activities against fish pathogenic bacteria in a range of 13.02-13.88 mm.…”
mentioning
confidence: 62%
“…However, the reports of its antimicrobial activity vary, sometimes with contradictory findings. The type of chitosan (e.g., molecular weight, degree of deacetylation) and other external factors (e.g., target organism, test methodology) may explain the unpredictability of its antimicrobial activity. As indicated in our results, none of the experimental resin‐based sealants and controls indicated halos of inhibition surrounding the discs or inhibition by contact against S. mutans .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Jiang et al . () reported no inhibition zone determined by a disc diffusion method for Salmonella at 24‐h exposure to 67 kDa chitosan. Rodríguez‐Núñez et al .…”
Section: Salmonella Typhimuriummentioning
confidence: 94%
“…Inconsistent antimicrobial activities of chitosans against S. Typhimurium have been reported. For instance, Jiang et al (2013) reported no inhibition zone determined by a disc diffusion method for Salmonella at 24-h exposure to 67 kDa chitosan. Rodr ıguez-N uñez et al (2012) observed a 2 Log CFU mL À1 (from 6.4 to 4.0) reduction of S. Typhimurium subjected to 0.1% chitosan with approximately 135 kDa.…”
Section: Salmonella Typhimuriummentioning
confidence: 99%